2013
DOI: 10.1186/1916-0216-42-59
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of a postoperative clinical care pathway in head and neck surgery with microvascular reconstruction

Abstract: BackgroundThe objective of this study is to evaluate the cost-effectiveness of a postoperative clinical care pathway for patients undergoing major head and neck oncologic surgery with microvascular reconstruction.MethodsThis is a comparative trial of a prospective treatment group managed on a postoperative clinical care pathway and a historical group managed prior to pathway implementation. Effectiveness outcomes evaluated were total hospital days, return to OR, readmission to ICU and rate of pulmonary complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…Our postoperative care pathway is associated with decreased health care utilization and inpatient costs in the 3 months after discharge from the hospital. We have previously reported that our pathway significantly reduced costs during the inpatient recovery period . Studying postdischarge resource utilization allowed us to determine if well‐designed and delivered inpatient care had persistent effects even after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our postoperative care pathway is associated with decreased health care utilization and inpatient costs in the 3 months after discharge from the hospital. We have previously reported that our pathway significantly reduced costs during the inpatient recovery period . Studying postdischarge resource utilization allowed us to determine if well‐designed and delivered inpatient care had persistent effects even after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Pathways outline the timing and coordination of all essential interventions provided by multiple health care disciplines in order to minimize delays, omissions, and duplications of care and therefore maximize effectiveness and efficiency . We have previously shown that implementation of a postoperative care pathway in patients undergoing major head and neck oncologic surgery with microvascular reconstruction was cost‐effective during the inpatient recovery period …”
Section: Introductionmentioning
confidence: 99%
“…In addition, well over a quarter of patients experience some postoperative complication such as pneumonia, wound disruption, and cardiac events . Knowledge of these potential complications can be used to counsel patients during the informed consent process . Because patients undergoing head and neck free tissue transfer are often of advanced age, present with multiple comorbidities, have a history of alcohol and tobacco use, and may have history of prior chemoradiation, any additional patient‐specific information regarding surgical risk would be useful in the clinical decision‐making process.…”
Section: Introductionmentioning
confidence: 99%
“…Other oncogenic HPVs are rarely detected in head and neck cancers . Molecular and epidemiologic studies suggest that HPV‐positive OPSCC comprise a distinct disease entity, which has a better prognosis . Immunohistochemistry using p16 has been used as a surrogate marker of oncogenic HPV and is now widely accepted …”
Section: Introductionmentioning
confidence: 99%